Effect of pulse frequency on the microstructure and properties of laser cladding layer of AlCoCrFeNiMo high entropy alloy - Wei Zhao; Xiang Li; Jinpeng Bi; Shuai Li; Chuanxin Fang; Hui Zhang; Song Gao; Yuexia Lv; Guangchun Xiao (Journal of Materials Research and Technology, 2024)
The cladding layer of high entropy alloy (HEA), specifically AlCoCrFeNiMo, was fabricated using both continuous wave (CW) and pulse wave (PW) laser techniques, with pulse frequencies set at 0.5 Hz, 5 Hz, 50 Hz, 500 Hz, and 5000 Hz. The microstructure of the cladding layer was analyzed using X-ray diffraction, ultra-depth-of-field metallographic microscopy, and scanning electron microscopy. The wear resistance, corrosion resistance, and combined corrosion-wear resistance of the cladding layer were assessed using friction and wear tests, electrochemical corrosion tests, and corrosion-wear experiments. Additionally, the impact of pulse frequency on the microstructure and properties of HEA cladding layers was examined and compared with CW cladding layers. The research results indicate the presence of body-centered cubic (BCC), σ, and B2 phases in all cladding layers. Compared to the CW cladding layer, the PW cladding layer exhibits smaller grain sizes and a reduced proportion of the σ phase. With an increase in pulse frequency, there is a gradual increase in the proportion of the σ phase and a corresponding evolution in the grain sizes within the HEA cladding structure. Notably, at a specific pulse frequency of 50 Hz, the grain size reaches its minimum. PW cladding exhibited superior wear resistance, corrosion resistance, and corrosion-wear resistance compared to CW cladding, primarily due to the finer grain size observed in the former. The optimal performance of the cladding layer can be achieved when the pulse frequency was set at 50 Hz. The refinement of grain size, combined with an appropriate presence of the σ phase, synergistically contributes to enhancing cutting resistance during friction processes. This collaborative effect further hinders plastic deformation, consequently improving the wear resistance of HEA cladding. Furthermore, the grain refinement in PW cladding promotes the development of surface oxide films, which play a crucial role in reducing galvanic corrosion of alloying elements and minimizing oxygen atom diffusion rates during corrosion processes. Consequently, both corrosion resistance and corrosion wear resistance of PW cladding are significantly enhanced.